#MeToo for Whom? Sexual Assault Disclosures Before and After #MeToo - Palmer, Jane E. (American journal of criminal justice, 2021)
In October 2017, #MeToo became a global hashtag for victims of sexual assault and harassment. In this study, we examine the extent of unwanted sexual experiences and disclosure, as well as perceptions of #MeToo, to assess differences among students who were represented and underrepresented in #MeToo coverage. Using a stratified random sample of students at a private university in the mid-Atlantic region of the U.S., we analyzed data from cross-sectional surveys conducted in March 2017 ( n = 1722) and March 2019 ( n = 1503). Results suggest that, relative to White students, in 2019 compared to 2017, there was an increase in disclosures among Black students and a decrease among Multiracial students. There was also an increase in undergraduate students who indicated ever experiencing unwanted sexual activity in 2019. Students who believed #MeToo affected how they think about past experiences were more likely to have indicated past experiences with unwanted sexual activity. Results also suggest that cisgender women, LGBQ, white, and multiracial students are at increased risk of unwanted sexual activity. However, Asian students, cisgender men, and non-LGBQ students may be less likely to disclose unwanted sexual activity. Implications for evaluating long-term impacts of #MeToo are discussed, along with suggestions for future research.